The longitudinal study on the reciprocal effects between GPA and burnout in university students: exploring grit, self-efficacy, and resilience as moderators - Puah, Shermain; Lim, Sok Mui; Kok, Xiao-Feng Kenan; Devilly, Oran (Frontiers in Education, 2024)
The current work aims to extend our understanding of the relationship between academic performance and burnout. Using longitudinal data collected from 521 students enrolled in a Singapore-based university from their freshmen year up to the end of year two, we examined the temporal order of the GPA-burnout relation to determine if there is a reciprocal relation between students’ burnout and academic performance. Grit, grit-passion, grit-perseverance, self-efficacy, and resilience were tested as moderating factors that were thought to potentially exacerbate, or protect against, the negative effects between GPA and burnout. Employing a panel analysis by means of SEM revealed that the relationship between GPA and burnout in our data is one where higher GPA contributes to worse burnout. Of all the moderating factors, only grit-passion was found to moderate the relationship between GPA and burnout, indicating that this relationship also depended on whether one has high or low grit-passion. In practice, our findings imply that high-achieving students are at risk of experiencing burnout due to excessive pressure and constant striving for better performance, but cultivating passion and enjoyment for academic activities can serve as a protective factor against burnout.